Performance evaluation of cyclone separator for air pollutant removal under varying conditions - Mohamed A. Mahmoud (Journal of Taibah University for Science)
In this work, an experimental air purification cyclone unit was designed for the separation of sawdust from the polluted air stream by the use or combination of centrifugal and gravitational force. Various parameters (sold loading, inlet velocity, pressure drop, particle size, moisture and density of feed material) were studied to obtain the optimal working conditions. The outcomes revealed that the cyclone efficiency grows from 95% to 98% when the inflow velocity increases from 3.75 to 6.24 m/s. Also, the cyclone efficiency increased by increasing the particle size, sold loading, and density. The pressure drop exhibits a linear increase with the inlet gas velocity and a linear decrease with sold loading. Furthermore, the feed moisture content of the inlet flow increases cyclone efficiency up to 40% and then the overall separation efficiency was decreased. Maintaining optimal moisture levels is crucial to ensuring that the cyclone performs efficiently without operational issues.